The central role of the reputation of country-of-origin firms in developing markets. Issue 3 (4th April 2016) - Jiménez, Nadia; San-Martin, Sonia
Abstract : Purpose: This study aims to test the central role of the perceived reputation of country-of-origin (COO) firms between cultural and socio-psychological variables and management and economic variables that help to explain the multi-faceted phenomenon of COO on a developing market. It also tests the moderator role of ethnocentrism, which is the objective of recommending different segment marketing strategies for international firms. Design/methodology/approach: The study opted for the structure equation modelling methodology to analyze data collected from 274 Mexican car owners who evaluate Korean automobiles. Findings: The results show that the COO reputation of firms from a developing market has a mediating role on the relationship between cultural openness and animosity and trust, risk and purchase intention, but the consequents of the perceived reputation of COO vary depending on the level of consumers' ethnocentrism. Research limitations/implications: Firms seeking to internationalize need to find out how to overcome the hurdle of target market animosity, to increase the cultural openness and to promote trust and purchases in international markets; at the same time, they reduce the perception of risk. In this sense, it might help to increase the perceived reputation of COO firms and to use different marketing strategies according to the target market. Originality/value: This study analyzes reputation of firms associated to a COO as a signal that can help to solve purchase decisions in the relationship between consumers and firms from developing markets and also corroborates its role as a mediator factor. In addition, this study empirically tests how animosity and cultural openness influence perceived reputation of COO firms, relationships that has scarcely been studied in literature. This study has also found that less and more ethnocentric consumers have differences in how the COO cues influence on their evaluations and behaviour. Finally, as insufficient consumer research has been conducted into emerging and developing markets, this study focuses on consumers from a developing country and regards automobiles from an emerging country.